The Strategy Of School Literacy Culture In Elementary School - Dyah Putri Fadillah; Istikomah Istikomah (Nazhruna: Jurnal Pendidikan Islam, 2021)
The purpose of the study is to know how the implementation strategies in SDN Bubutan IV Surabaya. The descriptive qualitative method is used in this analysis. The collecting data technique is using data reduction, data display, and conclusion drawing. The data validity test is using source triangulation. The result of the study showed that the school literacy movement strategies are already successful with (1) conditioned physical environment with mini-libraries in each classroom and student artworks around school areas, (2) conditioned the social environment as an effective model by giving rewards toward students, there is also an activity to celebrate a national holiday that integrated with literacy learning, and (3) conditioned the academic environment with an accustomed student to read 15 minutes, the existence of school literacy team and having a library with proper facilities.